Prospective evaluation of the safety of compounded bulk material L‐asparaginase in dogs with lymphoma. Issue 6 (17th April 2016) - Thiman, J.; Northrup, N.; Saba, C.; Clarke, D.; Regan, R.; Hamilton, T.; Lindell, H.; Hofmeister, E.
Abstract : Use of compounded L‐asparaginase became routine in veterinary oncology when manufacturing of Elspar ® was discontinued in 2012. The objective of this study was to evaluate the safety of compounded L‐asparaginase (CLASP, KRS Global Biotechnology, Boca Raton, FL, USA) in comparison with Elspar ® (Lundbeck LLC, Deerfield, IL, USA). In addition, we documented the response to CLASP in combination with a corticosteroid in this population of dogs with lymphoma. Dogs were prospectively treated with 10 000 IU/m 2 CLASP or Elspar ® subcutaneously. Corticosteroids were administered concurrently. Adverse events (AE) were assessed according to the Veterinary Cooperative Oncology Group Common Terminology Criteria for Adverse Events v1.1 (VCOG‐CTCAE). Response was recorded. Seventy‐three dogs received 75 treatments (CLASP, n  = 47; Elspar ®, n  = 28). No AE were attributed to CLASP. Grade I and II AE probably or possibly related to treatment were observed following two Elspar ® treatments. The overall response rate to the combination of CLASP and a corticosteroid was 80% (24% CR and 56% PR). In combination with a steroid, the compounded L‐asparaginase evaluated in this study is safe and demonstrates activity against canine lymphoma. In the face of the discontinuation of Elspar ®, veterinarians should seek compounded LASP products that have been tested for activity, purity, and sterility.